A Cross-Cultural Genre Analysis of Firm-Generated Advertisements on Twitter and Sina Weibo. (January 2022) - Shi, Xingsong; Wan, Wenjing
To investigate the generic features of firm-generated advertisements (FGAs) in cross-cultural contexts, this study analyzed 327 FGAs by Dell Technologies and the Lenovo Group on Twitter and Sina Weibo. Integrating affordances and multimodality into genre analysis, the study showed that the FGAs were characterized by (a) flexible move structure, (b) persuasive language, (c) visual illustration, and (d) hyperlinks, hashtagging (#), and mentioning (@) functions. The FGAs on Sina Weibo, compared with those on Twitter, tended to use more language play, emojis, and contextual product pictures and show more emphasis on the niche of products, incentives, and celebrity endorsement.